(untitled) (Research, Society and Development, 2022)
The Adolpho Ducke Forest Reserve is a fragment of the Amazon Rainforest that has the highest density of collections deposited in the INPA herbarium, and this characterized, vascular flora has been an important basis for chemical studies. This paper describes the chemical composition of the volatiles of aerial parts of the four species of Protium that occurr in the Ducke Reserve. The essential oils obtained by hydrodistillation were analyzed using GC-FID and GC-MS. P. altsonii showed high percentages of the monoterpenes α-pinene (22.05%) and limonene (17.76%) in the leaves, and linear long-chain fatty alcohols, such as n-tetradecanol (19.93%) and hexadecanol (32.56%), in the branches. The essential oil from leaves of P. laxiflorum provided sesquiterpenes α-copaene (18.98%), epi-α-cadinol (9.17%) and β-caryophyllene (9.04%) as the main compounds. In P. pallidum, the sesquiterpenes caryophyllene oxide (29.72%), α-cadinol (28.82%) and epi-α-cadinol (13.96%) were predominant in the leaves, and α-cadinol (25.50%), α-eudesmol (22.29%) and caryophyllene oxide (12.81%) predominated in the branches. β-Caryophyllene (30.59%) and caryophyllene oxide (20.63%) were the main compounds in the leaves of P. paniculatum var. riedelianum. The results presented herein contribute to the knowledge of the aromatic flora of the Ducke Reserve.